Synchronous semi-solid extrusion and photopolymerization of antimicrobial dressing hydrogel for wound healing - Mayur Jadhav; Peeyush Kumar Sharma; Shriram Mahajan; Sanjay K Banerjee; Santanu Kaity; Subham Banerjee (Carbohydrate Polymer Technologies and Applications, 2024)
Bacterial infections at wound sites require more time for a fast and efficient wound-healing process. Antibacterial methyl cellulose-based hydrogel wound dressing can be an excellent option because it can show antibacterial action, absorb wound exudates, and have a cooling and soothing effect on the wound bed. The ultraviolet (UV) ray-assisted semi-solid extrusion 3D printing technique was used to prepare 3D printed construct into a high surface area mesh-like structure utilizing UV radiation for photocrosslinking of hydrogel matrix in the presence of Poly (ethylene glycol) Diacrylate. The prepared hydrogel was characterized for contact angle, and rheological analysis before semi-solid extrusion-based 3D printing. After optimization of printing parameters, the 3D printed mesh was subjected to physicochemical characterizations like dimensional analysis, swelling study, drug content, in vitro drug release, and in vitro antimicrobial activity study. A rheological analysis confirmed the viscosity, thixotropy, and viscoelastic nature of prepared hydrogel. Drug release study showed approximately 50 % release in 4 h, and >80 % drug release in 24 h. After optimization of one batch, hydrogel polymerization was done by functional group analysis followed by validation of thread thickness by electron microscopy images and mechanical property assessment. The 3D-printed mesh was further evaluated for its in-vitro antibacterial performance against Escherichia coli and Staphylococcus aureus. The area of inhibition was one-fold more in Staphylococcus aureus and two-fold in E. coli, ensuring diffusion of the drug from 3D printed mesh and killing of bacteria. The work reported herein represents a universal platform to generate multifunctional and customized hydrogels with various functional substances for wound dressing applications.